E3 ubiquitin ligase MARCH5 positively regulates Japanese encephalitis virus infection by catalyzing the K27-linked polyubiquitination of viral E protein and inhibiting MAVS-mediated type I interferon production - Chenxi Li; Chenyang Tang; Xiqian Liu; Ying Liu; Linjie Zhang; Jing Shi; Qingyu Li; Mingan Sun; Yanhua Li (mBio)
ABSTRACT Membrane-associated RING-CH-type finger (MARCH) proteins, a class of E3 ubiquitin ligases, have been reported to be involved in the infection of multiple viruses and the regulation of type I interferon (IFN) production. However, the specific role and mechanisms by which MARCH proteins influence Japanese encephalitis virus (JEV) infection remain poorly understood. Here, we systematically investigate the functional relevance of MARCH proteins in JEV replication by examining the effects of siRNA-mediated knockdown of MARCHs on viral infection. We identified MARCH5 as a positive regulator of JEV replication. The knockout of MARCH5 dramatically reduced viral yields, whereas its overexpression significantly enhanced JEV replication. Mechanistically, MARCH5 specifically interacts with the JEV envelope (E) protein and promotes its K27-linked polyubiquitination at the lysine (K) residues 136 and 166. This ubiquitination enhances viral attachment to permissive cells. Substituting these lysine residues with arginine (R) attenuated JEV replication in vitro and reduced viral virulence in vivo. Furthermore, JEV infection upregulated the expression of MARCH5. We also discovered that MARCH5 degrades mitochondrial antiviral-signaling protein (MAVS) through the ubiquitin-proteasome pathway by catalyzing its K48-linked ubiquitination, thereby inhibiting type I IFN production in JEV-infected cells. This suppression of type I IFN further facilitates JEV infection. In conclusion, these findings disclosed a novel role of MARCH5 in positively regulating JEV infection and revealed an important mechanism employed by MARCH5 to regulate the innate immune response.IMPORTANCEJEV is the leading cause of viral encephalitis in many countries of Asia with an estimated 100,000 clinical human cases and causes economic loss to the swine industry. Until now, there is no clinically approved antiviral for the treatment of JEV infection. Although vaccination prophylaxis is widely regarded as the most effective strategy for preventing Japanese encephalitis (JE), the incidence of JE cases continues to rise. Thus, a deeper understanding of virus-host interaction will enrich our knowledge of the mechanisms underlying JEV infection and identify novel targets for the development of next-generation live-attenuated vaccines and antiviral therapies. To the best of our knowledge, this study is the first to identify MARCH5 as a pro-viral host factor that facilitates JEV infection. We elucidated two distinct mechanisms by which MARCH5 promotes JEV infection. First, MARCH5 interacts with viral E protein and mediates the K27-linked ubiquitination of E protein at the K136 and K166 residues to facilitate efficient viral attachment. Furthermore, double mutations of K136R-K166R attenuated JEV infection in vitro and reduced viral virulence in mice. Second, the upregulated expression of MARCH5 induced by JEV infection further suppresses the RIG-I-like receptor (RLR) signaling pathway to benefit viral infection. MARCH5 downregulates type I IFN production by conjugating the K48-linked polyubiquitin at the K286 of MAVS, which leads to MAVS degradation through the ubiquitin-proteasome pathway. In summary, this study provides novel insights into the role played by MARCH proteins in JEV infection and identifies specific ubiquitination sites on JEV E protein that could be targeted for viral attenuation and the development of antiviral therapeutics.